Analysis of Tarbawi Hadith about the Urgency of Science and Ulama Study of Contemporary Hadith - Nurul Hidayah; Ayu Rohmani Atasari (SCHOOLAR: Social and Literature Study in Education, 2021)
The importance of science in human life is unquestionable. In carrying out work from the smallest to the largest, humans need knowledge. In the Qur'an it can be seen that Allah declared Adam as vicegerent on earth, so he was prepared with knowledge. This was so that Adam was able to carry out his duties as caliph. The position of scholars and knowledge in Islam is really very high, this is clearly seen in the history of the Tarbawi Hadith which calls scholars as warasatul anbiya '(the heirs of the prophets). And among the most important for a scholar with his knowledge is sincere motivation (intention) in activities, in addition to sincere motivation, scholars are also humble, not arrogant to those who have contributed to him, must also be transparent in explaining knowledge. And what is meant by the author of this research gang is that it can be a means to find out the meaning of science and scholars in the perspective of contemporary tarbawi hadith studies. And knowing the affiliation (relationship) between science and scholars in the perspective of contemporary tarbawi hadith studies.